The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1158/1078-0432.ccr-21-3324
|View full text |Cite
|
Sign up to set email alerts
|

Convection Enhanced Delivery of the Oncolytic Adenovirus Delta24-RGD in Patients with Recurrent GBM: A Phase I Clinical Trial Including Correlative Studies

Abstract: Purpose: Testing safety of Delta24-RGD (DNX-2401), an oncolytic adenovirus, locally delivered by convection enhanced delivery (CED) in tumor and surrounding brain of patients with recurrent glioblastoma. Patients and Methods: Dose-escalation phase I study with 3+3 cohorts, dosing 107 to 1 × 1011 viral particles (vp) in 20 patients. Besides clinical parameters, adverse events, and radiologic findings, blood, cerebrospinal flui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Van den Bossche, Wouter BL, and colleagues found that the oncolytic adenovirus Delta24-RGD, also known as DNX-2401, shifted the murine GBM macrophage phenotype from the pro-tumoral M2 toward the antitumoral and pro-inflammatory M1 phenotype, thereby disabling a major tumor-maintaining mechanism [ 131 ]. Recently, a phase I clinical trial of DNX-2401 treating patients with recurrent GBM suggested increased numbers of macrophages and proinflammatory factors, including IL-6 and TNF-α, in posttreatment tumor specimens [ 132 ]. Virus vector-mediated cancer gene therapy aimed at macrophage reprogramming is also under investigation.…”
Section: Gam-targeted Therapy In Gbmmentioning
confidence: 99%
“…Van den Bossche, Wouter BL, and colleagues found that the oncolytic adenovirus Delta24-RGD, also known as DNX-2401, shifted the murine GBM macrophage phenotype from the pro-tumoral M2 toward the antitumoral and pro-inflammatory M1 phenotype, thereby disabling a major tumor-maintaining mechanism [ 131 ]. Recently, a phase I clinical trial of DNX-2401 treating patients with recurrent GBM suggested increased numbers of macrophages and proinflammatory factors, including IL-6 and TNF-α, in posttreatment tumor specimens [ 132 ]. Virus vector-mediated cancer gene therapy aimed at macrophage reprogramming is also under investigation.…”
Section: Gam-targeted Therapy In Gbmmentioning
confidence: 99%
“…There are numerous advantages to oncolytic viral approaches for reversing immune suppression in the tumor microenvironment: first, viruses are inherently pro-inflammatory, especially when replication-competent, inducing local pro-inflammatory cytokine and chemokine production and recruitment and activation of leukocytes; second, lysis of tumor cells can serve as an in situ vaccination, releasing antigens for detection by T cells, thereby potentially broadening the antitumor immune response; and third, viruses can be engineered to transduce target cells with numerous genes, enabling supra-physiologic pro-inflammatory stimuli, targeting multiple immune-suppressive mechanisms, and safety features such as ‘on-off’ switches. Several modified viral species, including herpes simplex virus, adenovirus, adeno-associated virus, and poliovirus are under development, primarily focused on the treatment of high-grade glioma (grades 3 and 4) [53,54 ▪▪ ,55 ▪▪ ,56,57], with encouraging preliminary results and multiple studies are in the process of recruitment (Table 2).…”
Section: Oncolytic Viral Therapymentioning
confidence: 99%
“…An inherent difficulty in investigating immune responses in oncolytic viral trials is that window-of-opportunity studies, in which treatment is administered before surgery, is challenging for safety and logistical reasons. This study and the study previously discussed were limited to an intratumoral investigation that was performed postmortem in two patients [54 ▪▪ ,56]. DNX-2401 is also being tested in a phase I trial in which patients receive virus-loaded allogeneic mesenchymal stem cells intra-arterially (NCT03896568; Table 2).…”
Section: Oncolytic Viral Therapymentioning
confidence: 99%
“…Other viral vectors utilizing replication-competent adenoviral vectors (Delta24-RGD) are also being investigated in recurrent gliomas. A recent Phase I clinical trial in current gliomas demonstrated that nearly 20% of patients had tumor responses after treatment with Delta24-RGD with increased peritumoral cytokine levels and tumor-infiltrating lymphocytes [ 62 ]. Additionally, other oncolytic virotherapies such as Delta-24-ACT that co-express immunostimulatory ligands are also being investigated in preclinical models to stimulate a robust antitumor immune response [ 63 ].…”
Section: Development and Refinement Of Glioblastoma Treatmentsmentioning
confidence: 99%